2016
DOI: 10.6018/analesps.32.3.224751
|View full text |Cite
|
Sign up to set email alerts
|

Physical disgust, germ aversion and antifat attitudes: the mediational effect of perceived controllability of weight

Abstract: Título: Asco físico, aversión a los gérmenes y actitudes antiobesos: el efecto mediacional de la percepción de controlabilidad del peso. Resumen: Las actitudes antiobesos se refieren a los estereotipos basados en el peso de las personas. Una posible explicación de las actitudes negativas hacia las personas obesas se basa en las reacciones emocionales suscitadas por el sobrepeso. En este estudio, realizado con 373 mujeres, se sugiere que el asco físico, la aversión a los gérmenes y la percepción de controlabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Some authors suggest that disgust may have evolved to perform the function of disease avoidance (Tybur et al, 2009). Recently, it has been found that both disgust and perceived vulnerability to disease were related to the expression of antifat attitudes (Magallares & Morales, in press).…”
Section: Studymentioning
confidence: 99%
“…Some authors suggest that disgust may have evolved to perform the function of disease avoidance (Tybur et al, 2009). Recently, it has been found that both disgust and perceived vulnerability to disease were related to the expression of antifat attitudes (Magallares & Morales, in press).…”
Section: Studymentioning
confidence: 99%